Penerapan Teknologi Untuk Menilai Status Gizi Pada Balita (Journal of Health Educational Science And Technology, 2022)
Parents need to notice attention to the nutritional status of toddlers to prevent nutritional disorders. Therefore, we need a system that can make it easier for parents to access information about the nutritional status of toddlers. The system that can be used is a technology system. The author conducted a literature analysis with a simplified approach in 10 technology journals for assessing the nutritional status of children under five for the 2012-2022 period. Based on this research, the authors conclude that technology to assess nutritional status in toddlers is very effective because it makes it easier for health workers to assess and record nutritional status, it makes it easier for parents to know the nutritional status of their toddlers, but in this study several things that still need to be considered include: understanding the use of technology for parents, the readiness of tools such as smartphones or other software that can be used to access technology to assess the nutritional status of toddlers.